Acupuncture as a tool to combat female infertility in healthcare: A literature review (Research, Society and Development, 2024)
Introduction: There is a prevalence of female infertility worldwide due to several factors, which may include marital status, education, unfavorable lifestyle, increase in reproductive diseases, artificial abortion, age, prolonged use of contraceptives and increased environmental pollution, but acupuncture has proven to be effective, making it possible to apply to the population regardless of social class. Objective: to describe the effectiveness of Acupuncture in tackling Female Infertility as a tool in individualized care for the female population. Method: This is a literature review, which searched for online studies carried out from February 2023 to April 2023 in electronic databases in virtual libraries. Discussion: Studies have shown that acupuncture has the necessary effect and is an instrument that can be used to combat female infertility, in which points can be used on the meridians of the kidneys, heart, liver, among others. Considerations: Acupuncture has contributed to the treatment of female infertility, presenting positive effects, therefore, one patient will never receive exactly the same treatment as another.